Chemical Vapor Deposition of High‐Quality Large‐Sized MoS2 Crystals on Silicon Dioxide Substrates. Issue 8 (31st March 2016) - Chen, Jianyi; Tang, Wei; Tian, Bingbing; Liu, Bo; Zhao, Xiaoxu; Liu, Yanpeng; Ren, Tianhua; Liu, Wei; Geng, Dechao; Jeong, Hu Young; Shin, Hyeon Suk; Zhou, Wu; et al.
Abstract : Large‐sized MoS2 crystals can be grown on SiO2 /Si substrates via a two‐stage chemical vapor deposition method. The maximum size of MoS2 crystals can be up to about 305 μm. The growth method can be used to grow other transition metal dichalcogenide crystals and lateral heterojunctions. The electron mobility of the MoS2 crystals can reach ≈30 cm 2 V −1 s −1, which is comparable to those of exfoliated flakes.